(untitled) (African Journal of Law and Politics, 2025)
Over the years, global trends have tilted towards diverse areas for sustainability most specifically on forest management. Forest provides a wide range of tangible and intangible benefits which cannot be over-emphasised. To indigenous communities, forest does not only provide them tangible benefits but also serves as an arena for their spiritual significance. It is mindful of these benefits that plethora of legal instruments have been enacted in Cameroon with several amendments to integrate the values forest holds for indigenous communities. Reflecting on these, this paper adopted the doctrinal and comparative research methods, to investigate and examine the integration of indigenous rights to forest within the scope of the 1994 Forestry Law to the recent 2024 Forestry Law. Consequently, this article has as its findings that the 2024 Forestry Law brings remarkable innovations firstly by attempting a broad definition of indigenous communities, forest, promises to incorporate their customary rights, provides these communities with benefit sharing incentives from forestry fees, enhances traditional hunting by creating community protected areas, community-managed hunting areas and gives these communities the opportunity to market such products which where very much limited in the 1994 Forestry Law. This article, therefore concludes that indigenous peoples have gone pass mere use and withdrawal rights to use, access, withdrawal and management rights under the present forest management scheme. However, these rights are very much temporary with no right of ownership thus impedes the complete realisation of their rights to forest.